Concentration Method of Nanobubble Aqueous Solutions at External Electric Field - Ri, Hyokmin; Jang, Gum Chol (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2025)
Nanobubbles have been widely applied in wastewater treatment, cleaning, medical and agricultural fields. The concentration of nanobubbles in nanobubble solutions generated by different nanobubble generation methods is very small, as low as <109 ml-1 (0.001 vol%). So, it is difficult to measure the size and concentration of the generated nanobubble solutions using a laser particle size analyzer (LPSA). To solve this problem, we proposed a method to concentrate nanobubble solutions using an external electric field. To account for the feasibility of the proposed method, the concentration process is simulated using “COMSOL Multiphysics” program. Based on the simulation results, the concentration experiments of nanobubble solutions prepared by ultrasonic cavitation is carried out. The measurements of the nanobubble solution before and after concentration using the LPSA device confirmed that the nanobubble solution can be concentrated by applying an external electric field.